Pengaruh Koordinasi Mata Tangan Dan Percaya Diri Terhadap Kemampuan Dribbling Pada Permainan Bola Basket Siswa SMAN 2 Soppeng - Alif Tunru, Andi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
The purpose of this research is (1) to determine whether there is an influence of eye-hand coordination on dribbling ability in basketball games among students at SMAN 2 Soppeng. (2) to find out whether there is an influence of self-confidence on dribbling ability in basketball games among students at SMAN 2 Soppeng. (3) to determine whether there is an influence of eye-hand coordination and self-confidence on dribbling ability in basketball games among students at SMAN 2 Soppeng. This research is of a descriptive and inferential nature. The target population is all students at SMAN 2 Soppeng, while the accessible population in this study consists of the 2nd-grade science and social science classes. The sample in this research is 30 male students from SMAN 2 Soppeng, selected through simple random sampling. The results of this study indicate that (1) there is a significant influence of eye-hand coordination on dribbling ability in basketball games among students at SMAN 2 Soppeng, amounting to 72.2%. (2) There is a significant influence of self-confidence on dribbling ability in basketball games among students at SMAN 2 Soppeng, amounting to 73.5%. (3) There is a significant influence of eye-hand coordination and self-confidence on dribbling ability in basketball games among students at SMAN 2 Soppeng, amounting to 81.1%. Keywords: Eye-Hand Coordination, Self-Confidence, Dribbling Ability